2004
DOI: 10.1615/jenvpathtoxoncol.v23.i1.70
|View full text |Cite
|
Sign up to set email alerts
|

p53 Binding to Target Sites Is Dynamically Regulated Before and After Ionizing Radiation-Mediated DNA Damage

Abstract: Although radiation therapy has been an important modality for cancer treatment, the molecular mechanisms underlying the overall genomic response of mammalian cells to radiation are not well characterized. The success of radiation therapy using ionizing radiation relies upon the regulation of both the cell cycle and apoptosis, as conferred by the activation of DNA damage-responsive genes. To better understand the key players involved in this response, expression-profiling experiments were performed using custom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our ChIP data suggested ubiquitous recruitment of Sin3B/HDAC1 on three p53-repressed promoters viz HSPA8 , MAD1 and CRYZ. Previous studies have suggested a dynamic binding of p53 to its target sites before and after stress/DNA damage [37][39]. Consistent with these finding, we also show recruitment of p53 and Sin3B at the p53-target sites both before and after Adriamycin treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Our ChIP data suggested ubiquitous recruitment of Sin3B/HDAC1 on three p53-repressed promoters viz HSPA8 , MAD1 and CRYZ. Previous studies have suggested a dynamic binding of p53 to its target sites before and after stress/DNA damage [37][39]. Consistent with these finding, we also show recruitment of p53 and Sin3B at the p53-target sites both before and after Adriamycin treatment.…”
Section: Discussionsupporting
confidence: 92%
“…45 Moreover, chromatin immunoprecipitation (ChIP) analyses demonstrated specific E2F4 recruitment to the promoter binding sites of PTTG1 and BUB3. In contrast, E2F4 was bound constitutively to Cdc6, an observation similar to the constitutive chromatin binding by p53 to its target promoters, 46 indicating the involvement of other factors or post-transcriptional regulation for their activation. PTTG1, BUB1, BUB3, Mad2, and CENP-E are mitotic checkpoint proteins (Fig.…”
Section: E2f Family Proteins: From Dna Damage To a Stable G 2 Arrestmentioning
confidence: 71%
“…It is expected that studies on gene expression at large scale may contribute to clarify the mechanism underlying cellular resistance to radiotherapy. In fact, reports about modulation of gene expression in response to IR in tumor cell lines, such as leukemia, 10 lymphoma, 11 cervical 12 and lung cancer 13 have indicated a list of radiation-responsive genes, but quantitative and qualitative differences have been found among different studies.…”
Section: Introductionmentioning
confidence: 99%